2011
DOI: 10.1007/s12225-011-9275-y
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic revision of unifoliolate Chinese Epimedium L. (Berberidaceae)

Abstract: Five Chinese species of Epimedium (Berberidaceae), E. simplicifolium T. are the only species of the genus previously described with unifoliolate leaves. Here, the authors review these five species based on extensive examination of specimens in herbaria and careful observation in the field and garden. E. simplicifolium is treated as a synonym of E. acuminatum Franch., and with the exception of E. elachyphyllum, the taxa are found to have predominantly trifoliolate and only occasionally unifoliolate leaves. Neot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…Epimedium comprises approximately 57 species, and only 5 of them (i.e., Epimedium brevicornu , Epimedium sagittatum , Epimedium koeanum , Epimedium pubescens and Epimedium wushanense ) are officially recorded in the Pharmacopoeia of the People's Republic of China (Zhang et al . ). Among them, Epimedium brevicornu was frequently employed to produce functional foods such as healthy tea, noodles, bread and alcoholic beverages (Zhang et al .…”
Section: Introductionmentioning
confidence: 97%
“…Epimedium comprises approximately 57 species, and only 5 of them (i.e., Epimedium brevicornu , Epimedium sagittatum , Epimedium koeanum , Epimedium pubescens and Epimedium wushanense ) are officially recorded in the Pharmacopoeia of the People's Republic of China (Zhang et al . ). Among them, Epimedium brevicornu was frequently employed to produce functional foods such as healthy tea, noodles, bread and alcoholic beverages (Zhang et al .…”
Section: Introductionmentioning
confidence: 97%
“…Our study clearly shows that the number and insertion of the leaves and the number of leaflets varies in this species. Upon extensive specimen examination, Zhang et al (2011, 2015b) observed that the leaves of E. simplicifolium T. S. Ying were mainly unifoliolate, occasionally trifoliolate, and the leaves of E. acuminatum Franch. may be unifoliolate.…”
Section: Discussionmentioning
confidence: 99%
“…may be unifoliolate. Subsequently, E. simplicifolium was synonymized with E. acuminatum (Zhang et al 2011). Hence, as a taxonomist, it is important to study as many collections as possible (Xu 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Ying was described by Ying (1975), only separating it from Epimedium acuminatum in having unifoliolate, sericeous leaves. Upon extensive specimen examination, however, Zhang et al (2011) found that the diagnostic characters of Epimedium simplicifolium were within the range of morphological variations of Epimedium acuminatum and placed Epimedium simplicifolium into synonymy.…”
Section: Taxonomic Treatmentmentioning
confidence: 98%